Capturing and communicating impact of citizen science for policy: A storytelling approach. (1st October 2021) - Wehn, Uta; Ajates, Raquel; Fraisl, Dilek; Gharesifard, Mohammad; Gold, Margaret; Hager, Gerid; Oliver, Jessie L.; See, Linda; Shanley, Lea A.; Ferri, Michele; Howitt, Camden; Monego, Martina; et al.
Abstract: In response to the need for approaches to understand how citizen science is currently influencing environmental policy and associated decision making, we devised the Citizen Science Impact StoryTelling Approach (CSISTA). We iteratively designed instruments to be used as tools primarily for citizen science practitioners seeking to understand or communicate policy impacts. We then trialled the CSISTA and associated instruments on four exemplary citizen science initiatives, using different forms of inquiry and collaboration with respective initiative leaders. In this paper, we present CSISTA, with details of the steps for implementing inquiry and storytelling instruments. Additionally, we reflect on insights gained and challenges encountered implementing the approach. Overall, we found the versatility and structure of CSISTA as a process with multiple guiding instruments useful. We envision the approach being helpful, particularly with regards to: 1) gaining an understanding of a citizen science initiative's policy and decision-making impacts; 2) creating short policy impact stories to communicate such impacts to broader audiences; or 3) fulfilling both goals to understand and communicate policy impacts with a unified approach. We encourage others to explore, adapt, and improve the approach. Additionally, we hope that explorations of CSISTA will foster broader discussions on how to understand and strengthen interactions between citizen science practitioners, policy makers, and decision makers at large, whether at local, national, or international scales. Highlights: Need to understand how citizen science influences environmental policy. Need to know how to communicate with policy makers and other stakeholders. The CSISTA approach supports citizen science leaders. The tools can help understand or communicate their policy impacts. Impact stories can demonstrate the value of citizen science to policy makers.